Bleeding risk of endoscopic ultrasound‐guided fine‐needle aspiration in patients undergoing antithrombotic therapy. Issue 1 (25th July 2016) - Inoue, Tadahisa; Okumura, Fumihiro; Sano, Hitoshi; Kobayashi, Yuji; Ishii, Norimitsu; Suzuki, Yuta; Fukusada, Shigeki; Kachi, Kenta; Ozeki, Takanori; Anbe, Kaiki; Iwasaki, Hiroyasu; Mizushima, Takashi; et al.
Abstract: Objectives: Bleeding events related to endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) are rare. However, for patients treated with antithrombotic agents, the bleeding risk of EUS‐FNA is uncertain. Hence, the aim of this study was to assess the bleeding event rate associated with EUS‐FNA in patients receiving antithrombotic treatment. Methods: A retrospective study was conducted in 742 consecutive patients who underwent EUS‐FNA for solid lesions between 2008 and 2015. We compared the bleeding event rates among patients who were not administered antithrombotic agents, those whose agent use was discontinued, those who continued treatment with aspirin or cilostazol, and those who were administered heparin as a replacement. Results: There were 131 patients (17.7 %) treated with antithrombotic agents. Seven experienced bleeding events, and the overall bleeding event rate was 0.9 % (7/742). All bleeding events were intraoperative; there were no postoperative bleeding episodes. Subgroup analysis by antithrombotic agent revealed bleeding event rates of 1.0 % (6/611), 0 % (0/62), 1.6 % (1/61), and 0 % (0/8) for the non‐administration, discontinuation of agents, continuation of aspirin or cilostazol, and heparin replacement groups, respectively. Only one severe bleeding event necessitated hemostatic treatment (1/742; 0.1 %); this occurred in a patient in the non‐administration group, and there were no severe bleeding events in patients receiving antithrombotic treatment. Conclusions: The present study found a low incidence of EUS‐FNA‐related bleeding in patients receiving antithrombotic treatment. The bleeding event rate was low even in patients who underwent EUS‐FNA while continuing aspirin or cilostazol.